THE SECOND GRADE STUDENTS' LEARNING MOTIVATION OF IMPLEMENTATION PROBLEM BASED LEARNING (PBL) ON GRAMMAR MATERIAL - Suciati Suciati; Dian Arief Pradana Pradana; St. Shabibatul Rohmah Rohmah (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Problem based leaning become one of teaching method ofimplementation instrusction. PBL required student to active duringleaning. Problem-based learning (PBL) is a self-directed learning strategywhere student work collaboratively in small group to investigate openendedrelatable case scenarios (Fukuzawa et al., 2017). Albanese et al in(Fukuzawa et al., 2017) wroten that Problem-based learning (PBL) canincreased student’s motivation and engagement in learning activity. It ismean that student have motivation to increase and engage active inlearning throught PBL. This research focus on achievemet motivationthat student have. This reseach used qualitative research method whichcover indentification, review the literatude,collect the data, analyze thedata and evaluate the research. questionnaires and interview used tocollect the data . Thirty four students enganged as participants. Based onthe data that was analyzed, the research present six things that motivatedthe student on grammar learning throught implementation PBL. Thoseare the role of grammar in english learning. The student’s spirit learning,More change to get achievement, PBL help student to show the ability inGrammar and english learning, Grammar is difficult. And feedback thathave sustainable effect in learning.